2020
DOI: 10.1186/s12964-020-00552-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of G-protein signaling, RGS2 and RGS4, inhibit protease-activated receptor 4-mediated signaling by forming a complex with the receptor and Gα in live cells

Abstract: Background: Protease-activated receptor 4 (PAR4) is a seven transmembrane G-protein coupled receptor (GPCR) activated by endogenous proteases, such as thrombin. PAR4 is involved in various pathophysiologies including cancer, inflammation, pain, and thrombosis. Although regulators of G-protein signaling (RGS) are known to modulate GPCR/Gα-mediated pathways, their specific effects on PAR4 are not fully understood at present. We previously reported that RGS proteins attenuate PAR1-and PAR2-mediated signaling thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 63 publications
(85 reference statements)
0
16
0
Order By: Relevance
“…To date, as the most potent negative regulator of G q α, RGS2 has been reported to act as a tumor suppressor in certain human cancers, such as breast, prostate, ovarian, and bladder cancers 18,32‐34 . A previous study stated that RGS2 can inhibit the activation of RhoA by negatively regulating heterotrimeric G protein signaling 35 . As a classical oncogene, RhoA is generally considered to be tumorigenic 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, as the most potent negative regulator of G q α, RGS2 has been reported to act as a tumor suppressor in certain human cancers, such as breast, prostate, ovarian, and bladder cancers 18,32‐34 . A previous study stated that RGS2 can inhibit the activation of RhoA by negatively regulating heterotrimeric G protein signaling 35 . As a classical oncogene, RhoA is generally considered to be tumorigenic 36 .…”
Section: Discussionmentioning
confidence: 99%
“…18,[32][33][34] A previous study stated that RGS2 can inhibit the activation of RhoA by negatively regulating heterotrimeric G protein signaling. 35 As a classical oncogene, RhoA is generally considered to be tumorigenic. 36 Similarly, high RhoA expression was closely associated with muscle invasion and metastasis in UCB.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, regulators of G protein signalling (RGS) eventually recognize the receptor and form complexes to terminate its signalling. Specifically, RGS2 interacts with G q and RGS4 interacts with G 12/13 , inhibiting the downstream processes of these G proteins [126]. Upon internalization, PAR-4 is sorted between lysosomes for degradation or endosomes for recycling [122].…”
Section: Par-4mentioning
confidence: 99%
“…Previous reported study synthesized the triazolone bearing compound Gαq-RGS2 signaling inhibitor and extensively evaluated the pharmacological activity against the urinary incontinence, which showed the beneficial activity in the urinary incontinence [ 4 ]. Furthermore, the Gαq-RGS2 signaling inhibitor has demonstrated Gαq signaling inhibitor activity by acting at the intersection of RGS2 and G-αq proteins, resulting in attenuated the Gαq signaling which reduced calcium fluxes and reduced muscle contraction [ 5 ]. In our previous study, we showed the beneficial effect of Gαq-RGS2 signaling inhibitor in the aminophylline induced cardiac arrhythmia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%